Local Wisdom Ulur-Ulur Tlaga Buret Ceremony in Tulungagung - Santoso, Eka Nurwaselina Santoso; Eko Wardani, Nugraheni; Anindyarini, Atikah (Humaniora: Journal of Indonesia Culture and Society, 2021)
The aims of the research were to describe the Ulur-ulur traditional ceremony, the procession, and the values of local wisdom in it. The research applied a qualitative study using a snowball sampling method with passive participant observation techniques and interviews. The researchers conducted in-depth interviews with note-taking and one-on-one interview techniques, namely by asking questions to the informants one by one and then recording the answers from the informants. The data validated by the source triangulation method were then analyzed using the Miles and Huberman research method which included data reduction, data presentation, and conclusion drawing. The research result shows that (1) the Ulur-ulur ceremony is one of the rituals that manifests the residents’ gratitude for the abundant water sources for the residents’ rice fields. (2) Ulur-ulur traditional ceremony procession consists of the preparation stage, jodhang procession, jamasan of Dewi Sri and Jaka Sedana statues, prayers and kajat, sowing flowers, and closes with a typical art performance of Tulungagung regency. (3) The practice of Ulur-ulur traditional ceremony has local wisdom values: religious, social, educational, historical, and economic values.